Investigation of interspersed shrubland patches along different topographical conditions within Afromontane grasslands, and their potential as conservation hotspots - Botham, Jason Lee (University of the Free State, 2020)
Smaller, isolated shrubland patches are often overlooked in the context of their ecosystem functions and potential for conserving biodiversity, particularly in relation to small scale areas of diversity importance within a specific conservation area. The mountainous Golden Gate Highlands National Park (GGHNP) possesses a number of these smaller, isolated shrubland patches, providing several habitat types over a relatively small geographical area. While these shrubland patches have been acknowledged as areas of possible significance in the GGHNP, information on arthropod assemblages in these patches remains limited. This thesis investigates arthropod assemblages in these smaller shrubland patches, in response to various environmental factors, and provides a preliminary view of the current state of gene flow among five ubiquitous spider species. Three aims were selected to investigate environmental factors and their influence on arthropod assemblages, while a fourth addressed gene flow and genetic diversity of spider species. In Chapter 2, we evaluate the effect of elevation and vertical stratification on arthropod species diversities and assemblages in shrubland patches present in the GGHNP. The results indicated differing environmental pressures between and within the sampled sites brought about by elevation and stratification. However, due to the relatively short elevational range and high heterogeneity of the localities, it is not conclusive as to whether elevation was the only factor responsible for differences in population diversities across the sites. Contrastingly, vertical habitat stratification influenced arthropod assemblage richness and composition despite the small vertical distance between strata. The study suggests that multiple contributing factors, together with stratification, affect arthropod assemblages. Investigations into seasonal variation and temporal change on arthropod populations may provide insight into the protective nature of smaller shrubland patches against environmental change and disturbance. Chapter 3 aimed to determine how arthropod assemblages vary with seasonal changes in three vertical habitat strata in these smaller shrubland patches, representing isolated shrublands in a grassland dominated montane environment subject to seasonal variation. Environmental variable changes temporally affected arthropod assemblages to differing degrees in each stratum, dependent on the level of disturbance. Beta-diversity was observed to gradually decrease for leaf litter across the localities. The study suggests that, depending on the level of protection of these patches, shrubland sites may act as high diversity zones during seasonal change as well as periods of disturbance. Chapter 4 investigated the differences in composition of soil arthropod assemblages, and their species association, with a number of isolated shrubland patches and their immediate surrounding grasslands. The results indicated a higher association of soil biota with shrubland patches compared to the adjacent grasslands while functional feeding groups were not discernibly different between the two habitat types. Results suggest that different soil arthropods are associated with shrubland patches of the GGHNP, hinting at their significance as areas of priority management for certain taxa and their importance in conservation strategies. The final study (Chapter 5), analysed the state of gene flow and inferred migratory capability of five spider species between shrubland patches of the GGHNP. Relatively low nucleotide diversity, with a correspondingly high genetic diversity, was observed within populations for all species except one. Differing genetic differentiation indicated gene flow as being maintained, to a certain degree, between populations of the spider species, despite the mountainous terrain of the park. Additionally, the presence of possible species complexes was inferred by phylogenetic analyses, highlighting a need for taxonomic revision of these species from a South African perspective. The results of this thesis provide a unique insight into the state of arthropod diversity, and their association with shrubland patches of the GGHNP, by investigating arthropod assemblage responses, and determining the current state of gene flow and genetic diversity of spider species.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2020
Keywords: Elevation; Soil; Spiders; Golden Gate Highlands National Park; Biota in soil; Shrubland patches; Arthropod populations; Conservation of biodiversity; Leaf litter; Arachnids; Stratification